African Asylum Seekers in Europe: The Interplay between Foreign Aid and Governance in Origin Countries - Jordi Ripollés; Inmaculada Martínez-Zarzoso (Open Economies Review, 2021)
This paper empirically investigates the effects of governance quality on the number of African asylum seekers in Europe over the period 1996–2018 and evaluates the extent to which official development aid acts as a catalyst. With this purpose in mind, different gravity model specifications and estimation approaches have been employed. The obtained results suggest that the asylum flows are strongly determined by governance quality in the country of origin and that this effect does depend on the amount of foreign aid received from developed countries. Moreover, it is also found that development aid is only effective in reducing asylum applications coming from countries with good governance. Moreover, we find no differences in the estimated elasticity of foreign aid on asylum claims for the beneficiaries of the European Union Emergency Trust Fund (EUTF) for Africa, the main aim of which has been to improve living conditions of potential migrants in their countries of origin.
Keywords: F35; O11; 9; 330; Asylum seekers; ODA; Africa; European Union; Governance; Gravity model